Shaping global industrial relations. The impact of international framework agreements (Geneva, 2011)
"n recent years, many multinational enterprises have adopted corporate codes of conduct with social provisions. Increasingly, they are now signing international framework agreements (IFAs) with global unions representing workers by sector of activity. In addition to regulating labour–management relations across global value chains, these agreements aim to promote compliance with ILO core labour standards. "